EVALUACIÓN POST-OCUPACIÓN DEL PABELLÓN PROF. PABELLÓN ANTONIO FERNANDO RODRIGUES (UERJ) DE LA SATISFACCIÓN DEL USUARIO - Jairo Ferreira Lopes de Farias; Solange Mathias de Almeida; Elenice Rachid da Silva; Thereza Cristina Ferreira Camello; Josimar Ribeiro de Almeida (Universidade do Estado do Rio de Janeiro, 2015)
Post Occupancy Evaluation defines the methods and techniques to characterize the strength and weaknesses of a constructed structure by considering the users satisfaction in meeting their needs during the course of its use. This evaluation records the findings of the POE of the Pavillon Prof. Antônio Fernando Rodrigues, Maracanã campus of the State University of Rio de Janeiro (UERJ), relative to the environmental quality from the satisfaction of users. Results of the evaluation of the degree of satisfaction of the users reveal a positive response towards artificial illumination, artificial ventilation, the temperature in winter and in summer and the natural illumination. In general it was found that users considered the building well lit, properly temperature controlled and of appropriate size, but needed better soundproofing. The analysis led to recommendations for improvements in comforts and functionality of this environment. These findings can contribute to the improvement for future projects, avoiding the repetition of inadequacies and the consequent dissatisfaction of users, and for better post-occupancy management.   DOI: http://dx.doi.org/10.12957/sustinere.2015.20004